2021
DOI: 10.1016/j.jpsychires.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk and protective factors associated with suicidal ideation during the COVID-19 pandemic in U.S. military veterans with pre-existing psychiatric conditions

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has negatively affected the mental health of the general population. However, less is known about its impact on vulnerable populations, such as veterans with pre-existing psychiatric conditions. Data were analyzed from the National Health and Resilience in Veterans Study, which surveyed a nationally representative cohort of U.S. veterans. Pre-pandemic and 1-year peri-pandemic risk and protective factors associated with suicidal ideation (SI) were examined in vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 65 publications
2
33
2
Order By: Relevance
“…In addition, veterans are more likely to have a history of psychiatric conditions, such as PTSD, suicidal behavior, and substance use disorders relative to the non-veteran population (Hoggatt, Lehavot, Krenek, Schweizer, & Simpson, 2017 ; Lehavot, Katon, Chen, Fortney, & Simpson, 2018 ; United States Department of Veterans Affairs Office of Mental Health & Suicide Prevention, 2019 ), which may be exacerbated by pandemic stressors (Murphy, Williamson, Baumann, Busuttil, & Fear, 2020 ). Indeed, one previous study of veterans with pre-existing psychiatric disorders found that pre-pandemic psychiatric symptom severity predicted suicide ideation during the pandemic (Na et al, 2021 ). Finally, relative to civilians, veterans have higher rates of medical morbidities such as cardiovascular disease, obesity, and diabetes (Hoerster et al, 2012 ; Lehavot, Hoerster, Nelson, Jakupcak, & Simpson, 2012 ), which may increase vulnerability to health-related stressors including risk of severe disease from COVID-19 infection and pandemic-related delays in obtaining routine health care (Földi et al, 2020 ; Ssentongo, Ssentongo, Heilbrunn, Ba, & Chinchilli, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, veterans are more likely to have a history of psychiatric conditions, such as PTSD, suicidal behavior, and substance use disorders relative to the non-veteran population (Hoggatt, Lehavot, Krenek, Schweizer, & Simpson, 2017 ; Lehavot, Katon, Chen, Fortney, & Simpson, 2018 ; United States Department of Veterans Affairs Office of Mental Health & Suicide Prevention, 2019 ), which may be exacerbated by pandemic stressors (Murphy, Williamson, Baumann, Busuttil, & Fear, 2020 ). Indeed, one previous study of veterans with pre-existing psychiatric disorders found that pre-pandemic psychiatric symptom severity predicted suicide ideation during the pandemic (Na et al, 2021 ). Finally, relative to civilians, veterans have higher rates of medical morbidities such as cardiovascular disease, obesity, and diabetes (Hoerster et al, 2012 ; Lehavot, Hoerster, Nelson, Jakupcak, & Simpson, 2012 ), which may increase vulnerability to health-related stressors including risk of severe disease from COVID-19 infection and pandemic-related delays in obtaining routine health care (Földi et al, 2020 ; Ssentongo, Ssentongo, Heilbrunn, Ba, & Chinchilli, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the overall prevalence of SI is 16.4% in the general population of China during the COVID-19 pandemic ( Shi et al, 2021 ). Moreover, 19.2% of veterans with pre-existing psychiatric conditions in the US screened positive for SI during the peri-pandemic period ( Na et al, 2021 ). A multivariable analysis has also linked greater pre-pandemic psychiatric symptom severity, past-year SI, lifetime SA, psychosocial difficulties, COVID-19 infection, and past-year increases in psychiatric symptom severity to peri-pandemic SI ( Na et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 19.2% of veterans with pre-existing psychiatric conditions in the US screened positive for SI during the peri-pandemic period ( Na et al, 2021 ). A multivariable analysis has also linked greater pre-pandemic psychiatric symptom severity, past-year SI, lifetime SA, psychosocial difficulties, COVID-19 infection, and past-year increases in psychiatric symptom severity to peri-pandemic SI ( Na et al, 2021 ). In addition, individuals with psychiatric disorders have a 1.64-fold higher risk of SI compared to those without disorders ( Papadopoulou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis provides that suicide attempt (SA) has 31% lifetime prevalence in individuals with major depressive disorder (MDD) across the world [2]. The topic of depression and suicide is unprecedentedly urgent and essential as the increased suicidality in the COVID-19 pandemic reported from different countries [3][4][5]. At present, clinical assessments of suicide risk usually rely on retrospective information, which are often unsatisfactory [6].…”
Section: Introductionmentioning
confidence: 99%